Detection of siloxane thin films on glass substrate using IR ratio-reflectance spectrum - Ivanovski, Vladimir; Piwoński, Ireneusz; Guziejewski, Dariusz; Mayerhöfer, Thomas G. (Elsevier BV, 2022)
In case of thin films of siloxane obtained from different organo-silane derivatives (alkoxy and chloro) on soda lime silica glass substrates, IR-ATR and IR-SR could not detect the organic functional groups of the coating. This becomes even more problematic for the case of tetraethoxysilane (when fully hydrolyzed), the coating of which possesses the same functional groups as the glass substrate. In this work we propose to employ the so-called ratio-reflectance spectra in the v(Si-O) wavenumber region, where both glass and the siloxane coating give most prominent bands, important for the evaluation of the quality of coating formation and qualitative knowledge on its structure. We show that the reflectance-absorbance spectra obtained from the ratio-reflectance spectra are in direct connection to the structure of the siloxane network which depends not only on the chemical nature of the parent silane, but also on the dipping time and the solvent composition. Some characteristics of the reflectance-absorbance spectra, like the appearance of a two well defined bands at 1110 and 975 cm-1, can be correlated to the film morphology and bridging oxygen number. We support our conclusions using principal component analysis of reflectance spectra, contact angle, AFM and SEM measurements.
Keywords: Specular reflectance spectrum, Thin films, Silane, Siloxane, Glass